Modelling agricultural changes and impacts at landscape scale: A bibliometric review. (December 2019) - Hossard, L.; Chopin, P.
Abstract: Understanding the range of approaches available for assessing the impacts of agricultural changes at landscape scale is important when addressing local to global issues. Using a topic modelling approach, we reviewed the literature on impact modelling of agricultural landscapes. A search in Web of Science using the keywords model, agricultural systems and landscape yielded 1, 975 hits, of which 514 papers met our selection criteria. The most salient terms fell within six groups: change, scale, pollution, biodiversity, practices and terms on biophysical/regulatory conditions. We identified four main topics: water quality, water quantity/energy crops, biodiversity and Integrated Assessment. Water management issues were more likely to be covered in North American researches, while issues related to Integrated Assessment were mainly covered in European studies. We found no relationship between topic and model type. We conclude that future integrated studies should consider the diversity of agricultural systems in governance of water and biodiversity issues. Highlights: We performed a topic analysis on a selected ensemble of 514 publications. Main topics were water quality, water quantity, biodiversity, Integrated Assessment. Biodiversity was the most recent topic to emerge. Biodiversity and water quality/quantity assessments were rarely combined. Agricultural practices should receive more attention in landscape approaches.